A multi-discipline approach linking related disciplines and stakeholder communities to develop business expertise for the new technological environment - Petrova, K.; Sinclair, R. (Australian Academic Press, 2000)
Although teaching institutions are typically well behind business in adopting new technologies, an attempt is being made at the Auckland University of Technology to introduce a new field of study and a new technological environment for its delivery - a comprehensive programme in eBusiness studies. The university works very closely with its stakeholder communities particularly in identifying new programme needs to ensure a balance is achieved between technical skill and business focus. As a result of this collaboration an operational model comprising a total of eight modules was constructed with the aim of integrating the proposed eBusiness qualifications within the structure of an existing Bachelor of Business degree. This paper discusses the background and development of a module called "Electronic Transactions and Security" and the interrelationship between other modules within the eBusiness field of study. The module comprises transaction processing, transaction security and risk management and has evolved into a multi-discipline partnership between the Accounting and Finance and Information Technology business disciplines. New digital technologies - such as on-line collaboration and on-line resource sharing and exchange will be an integral part of the teaching and learning process.